Web-technologies in Knowledge Integration as a Means of Mathematical Literacy Forming of School Students (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Digitalizing of social relations and new dominants of the younger generation entails a change in the requirements for mathematics teacher’s professional activity. A modern teacher should not only have the fundamental knowledge concerning with mathematics, but also possess the modern Web-technologies as a means and component of information and educational environment organizing and managing of functional literacy development of school students. The article deals with the components and techniques of mathematical literacy integration and information competence and procedures development in teaching mathematics on the basis of complex knowledge mastering in network educational community; the content and mechanisms for such integration, based on modern achievements in science adapting (fractal geometry, fuzzy sets and fuzzy logic, theory of coding and data encryption, etc.) to school mathematics is also revealed. Problems solving of universal educational actions and mathematical literacy development of school students as a structural phenomenon of an innovative educational environment organizing for managing the school student's cognitive activity in the network educational community is consistently reflected. The cognitive and activity-based aspects of the introduction of Web-technologies and information environments in the integration of mathematical literacy and information competence as well as school student’s cognitive activities are identified.